Performance evaluation of utility exchange-traded funds: A super-efficiency approach - Ioannis E. Tsolas (Journal of Risk and Financial Management, 2022)
Choosing funds is a general issue for investors, with the aim of balancing potential risks and returns. The aim of this article is to use a super-efficiency approach to analyze and rank exchange-traded funds (ETFs) in order to find the best utility ETFs. The range-adjusted measure (RAM)-based data envelopment analysis (DEA) model is used in this work to evaluate a set of utility ETFs and rank inefficient funds, while the super-efficiency RAM model is used to fully rank RAM-based efficient funds. Other slack-based selected DEA models are also used to analyze the ETFs. The results show that the suggested approach delivers the same efficient funds as other slack-based selected DEA models; hence, it appears to be useful as a fund selection tool.
Keywords: 650; data envelopment analysis; range-adjusted measure (RAM); super-efficiency; utility exchange-traded funds